Crystal Arthropathy in the Setting of Total Knee Arthroplasty - Joseph C. Brinkman; Kade S. McQuivey; Justin L. Makovicka; Joshua S. Bingham (Case Reports in Orthopedics)
We present a case of an 82-year-old female with a history of right total knee arthroplasty 11 years prior. She was admitted after a ground-level fall and developed progressive pain and swelling of her right knee. She had no history of complications with her total knee replacement. Radiographs of the knee and hip were negative for acute fracture, dislocation, or hardware malalignment. Knee aspiration was performed and revealed inflammatory exudate, synovial fluid consistent with crystal arthropathy, and no bacterial growth. She was diagnosed with an acute gout flare, and her symptoms significantly improved with steroids and anti-inflammatory treatment. Orthopedic surgeons should be aware of the potential for crystal arthropathy in the setting of total joint arthroplasty and evaluate for crystals before treating a presumed periprosthetic joint infection.